Role of circulating inflammatory protein in the development of diabetic renal complications: proteome-wide Mendelian randomization and colocalization analyses - Liu, Wenli; Zhang, Jiaqi; Zhang, Duo; Zhang, Lei (Frontiers in Endocrinology, 2024)
Background: Diabetes ranks among the most widespread diseases globally, with the kidneys being particularly susceptible to its vascular complications. The identification of proteins for pathogenesis and novel drug targets remains imperative. This study aims to investigate roles of circulating inflammatory proteins in diabetic renal complications.(FGF23) (OR 1.379, 95%CI 1.035-1.837, P=2.82×10 -2 ), C-C motif chemokine ligand 7 (CCL7) (OR 1.385, 95%CI 1.111-1.725, P=3.76×10 -3 ), and TNF superfamily member 14 (TNFSF14) (OR 1.244, 95%CI 1.066-1.451, P=5.63×10 -3 ) indicated potential risk factors for type 2 diabetes (T2D) with renal complications. Colocalization analysis supported these findings, revealing that most identified proteins, except for DNER, likely share causal variants with diabetic renal complications.Our study established associations between specific circulating inflammatory proteins and the risk of diabetic renal complications, suggesting these proteins as targets for further investigation into the pathogenesis and potential therapeutic interventions for T1D and T2D with renal complications.